Productivity of the crop rotation link with lupine with different methods of basic tillage - Е. I. Isaeva; G. L. Yagovenko (Зерновое хозяйство России)
The current paper has considered the study results of the productivity of the lupine-winter wheat rotation link with different methods of basic tillage. The study was carried out on grey forest soil in the south-west of the Blackearth part of the Bryansk region on the basis of the stationary trial of the All-Russian Research Institute of Lupine in 2015–2018. The purpose of the study was to characterize the productivity of the lupine – winter wheat crop rotation link with differ[1]ent methods of basic tillage. The scheme of the trial included four variants of the main tillage during the cultivation of winter wheat and lupine in a four crop rotation sequences, namely winter wheat – naked oats – winter triticale – lupine. During the period of the study, the highest productivity of the lupine-winter wheat rotation link was identified in the case of moldboard plowing with chisel tillage once every four years for lupine and amounted to 5.2 t/ha of grain units. With this method of tillage, winter wheat and lupine showed high rates of yield and nutritional value. These indicators turned out to be energetically beneficial in terms of energy flow in the agroecosystem. The lowest rates of yield of the link was obtained in the option with subsurface plowing to a depth of 16 cm and amounted to 3.9 t/ha of grain units; the energy cost per ton of grain was 6.7 GJ. With the option with traditional moldboard plowing, the productivity of the crop rotation link was 4.5 t/ha of grain units, and the energy cost was 5.9 GJ per ton of grain. All the presented options of the main tillage in this crop rotation can be used on farms with different levels of economic development and farming culture.